2022
DOI: 10.1111/pcmr.13030
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathogenesis of Hermansky–Pudlak syndrome

Abstract: Hermansky-Pudlak syndrome (HPS) is an autosomal recessiveMendelian disorder characterized by oculocutaneous albinism (OCA) or ocular albinism (OA), bleeding tendency, and ceroid deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 127 publications
0
16
0
Order By: Relevance
“…D) Quantification of the anti-JhI-21 signal in the nuclei of subperineurial (N=8-10) and perineurial (N=28-36) cells of the brains shown in (B). E) Quantification of the anti-JhI-21 signal in the nuclei of neurons (N= [18][19][20][21][22][23][24] shows no significant difference between pallidin knockdown and control conditions. *: p<0.05; **: p<0.005 ; *** : p<0.0005; Mann-Whitney between control and knockdown conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D) Quantification of the anti-JhI-21 signal in the nuclei of subperineurial (N=8-10) and perineurial (N=28-36) cells of the brains shown in (B). E) Quantification of the anti-JhI-21 signal in the nuclei of neurons (N= [18][19][20][21][22][23][24] shows no significant difference between pallidin knockdown and control conditions. *: p<0.05; **: p<0.005 ; *** : p<0.0005; Mann-Whitney between control and knockdown conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They display common phenotypes, originating from defects in highly specialized lysosome-related organelles, such as reduced pigmentation due to impaired retinal and epidermal melanosomes, or extended bleeding times resulting from the lack of dense granules in platelets. In humans, mutations in BLOC1 genes and other functionally related genes are found in the Hermansky-Pudlack syndrome, which is similarly characterized by albinism and increased bleeding time 19 . In addition, genetic studies have identified variants of the dysbindin gene and other BLOC1 genes as risk factors for developing schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ influx caused by SYT4 overexpression activates TRPM1 and MITF through CAMK4 ( Jia et al, 2020 ). Melanin is synthesized within the melanosomes, a type of lysosome-related organelles ( Li et al, 2022 ). Melanosome biogenesis/maturation is also regulated by Ca 2+ homeostasis in the melanosome.…”
Section: Introductionmentioning
confidence: 99%
“…Hermansky-Pudlak syndrome (HPS) is an autosomal recessive, genetically heterogenous disease resulting from the dysfunction of intracellular lysosomal trafficking. 1,2 HPS is characterized by oculocutaneous albinism (OCA), platelet deficiency and dysfunction, and, in some cases, pathologies of other organ systems such as pulmonary fibrosis, granulomatous colitis, cardiomyopathy, and systemic immunodeficiency. 1,2 Mutations in 11 genes have been identified in the pathogenesis of HPS, and the highest prevalence of HPS is found in Puerto Rico, where it affects 1 out of every 1800 people with a carrier rate of 1:21.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 HPS is characterized by oculocutaneous albinism (OCA), platelet deficiency and dysfunction, and, in some cases, pathologies of other organ systems such as pulmonary fibrosis, granulomatous colitis, cardiomyopathy, and systemic immunodeficiency. 1,2 Mutations in 11 genes have been identified in the pathogenesis of HPS, and the highest prevalence of HPS is found in Puerto Rico, where it affects 1 out of every 1800 people with a carrier rate of 1:21. 2,3 The most common types of HPS in Puerto Rico are HPS-1 and HPS-3, which present with varying rates of lung and colonic involvement.…”
Section: Introductionmentioning
confidence: 99%